2023
DOI: 10.1097/md.0000000000033810
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of anemia among human immunodeficiency virus-infected individuals in East Africa: A systematic review and meta-analysis

Abstract: Background: Human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) patients face several hematological abnormalities. Of these abnormalities, anemia is the most common one. Africa has a high prevalence of HIV/AIDS, especially in the East and South African region, which is heavily affected by the virus. Therefore, this systematic review and metaanalysis aimed to determine the pooled prevalence of anemia among patients with HIV/AIDS in East Africa.Methods: This systematic review and meta-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…Anemia patterns vary by study setting but have been reported to be as high as 85% [ 4 ]. The overall prevalence of anemia in this study was 63.6%, which is consistent with previous studies from various spots that found high rates: 64% in Nigeria [ 13 ], 71% in Isfahan, Iran [ 4 ], 69.7% in Benin [ 14 ], and 77.4% in Tanzania [ 15 ]. Even so, our percentage is higher than that of a number of other Asian and non-Asian countries, such as China (51.9%) [ 16 ], Ethiopia (34.6%) [ 17 ], northern India (16.2%) [ 18 ], South Africa (25.8%) [ 8 ], and Ghana (23.8%) [ 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…Anemia patterns vary by study setting but have been reported to be as high as 85% [ 4 ]. The overall prevalence of anemia in this study was 63.6%, which is consistent with previous studies from various spots that found high rates: 64% in Nigeria [ 13 ], 71% in Isfahan, Iran [ 4 ], 69.7% in Benin [ 14 ], and 77.4% in Tanzania [ 15 ]. Even so, our percentage is higher than that of a number of other Asian and non-Asian countries, such as China (51.9%) [ 16 ], Ethiopia (34.6%) [ 17 ], northern India (16.2%) [ 18 ], South Africa (25.8%) [ 8 ], and Ghana (23.8%) [ 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…This is due to increased access to antiretroviral therapy that has improved survival (Kharsany & Karim, 2016) . Hematological complications have been found to be a significant problem among PLWHIV worldwide, negatively impacting their quality of life and disease progression (Melese et al, 2017;Cao et al, 2022a;Getu et al, 2023;Sah et al, 2020;Sahle et al, 2017). In Africa, the prevalence of anemia in PLWHIV ranges between 16.2% to 69% (Ikolango et al, 2023;Zenebe et al, 2019).…”
Section: Introductionmentioning
confidence: 99%